The identification of depression in children and adolescents: main challenges found in primary health care (Research, Society and Development, 2021)
Depression is a mental disorder characterized by mood disorders, caused by the interaction of social, physical and environmental factors that most affect the world population. The intensity of symptoms can cause the patient social and psychological problems, which can lead to suicide. Organic and mental conditions, in addition to social and family requirements, make the children and adolescents vulnerable to the development of depression. The absence of standardized studies and tools makes the diagnosis difficult and late, increasing harm to the patient. We proposed to present in this qualitative and descriptive review a critical and detailed analysis of studies published in the last ten years related to depression in children and adolescents, the main validated tools used and difficulties in early diagnosis. Searches were performed on the Scielo®, MedLine® and PubMed® platforms using correlated descriptors. After inclusion and exclusion criteria, 22 articles were selected to integrate this review. Studies show that the association between analysis tools, such as semi-structured interviews, and the detection of symptoms through careful and careful analysis by psychologists and physicians facilitate the suspicion of this diagnosis in this age group. Thus, the information presented in this review is important for health professionals to have a better understanding of symptoms and more accurate validated tools for the diagnosis of depression in children and adolescents.